Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/bf02303857
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in pelvic exenteration: Factors responsible for reducing morbidity and mortality

Abstract: Routine use of prophylactic antibiotics, prophylactic subcutaneous heparin, and intensive postoperative monitoring appear to have reduced morbidity from pelvic exenteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 20 publications
4
50
0
4
Order By: Relevance
“…Today, combined pelvic surgery is used with curative intent in order to achieve radical resection and improve treatment results. According to latest data, a 5-year survival after pelvic exenteration is more than 50% [4][5][6][7]. Goldberg JM et al (1998) concluded that the indications for palliative exenteration should be exceptional and strictly individual, and, generally, this type of surgery should not be used for palliation [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, combined pelvic surgery is used with curative intent in order to achieve radical resection and improve treatment results. According to latest data, a 5-year survival after pelvic exenteration is more than 50% [4][5][6][7]. Goldberg JM et al (1998) concluded that the indications for palliative exenteration should be exceptional and strictly individual, and, generally, this type of surgery should not be used for palliation [5].…”
Section: Discussionmentioning
confidence: 99%
“…According to latest data, a 5-year survival after pelvic exenteration is more than 50% [4][5][6][7]. Goldberg JM et al (1998) concluded that the indications for palliative exenteration should be exceptional and strictly individual, and, generally, this type of surgery should not be used for palliation [5]. Nguen DQ et al (2005) have not shown any survival improvement after palliative pelvic exenteration [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo com os avanços observados na área de radioterapia e quimioterapia, a ressecção com margens livres ainda é o único tratamento capaz de oferecer chance de cura para pacientes portadores de tumores pélvicos localmente avançados (Brunschwing e Daniel, 1954;Bricker et al, 1960;Symmonds et al, 1975;Rutledge et al, 1977;Rodriguez-Bigas e Petrelli, 1996;Goldberg et al, 1998).…”
Section: Aspectos Cirúrgicosunclassified
“…No decorrer dos anos foram identificados fatores responsáveis pelos melhores resultados obtidos com essa cirurgia (Lopez et al, 1994;Goldberg et al, 1998).…”
Section: Morbidade E Mortalidade Pós-operatóriasunclassified
See 1 more Smart Citation